Smart learning environments: their concept, components, contexts, educational philosophy, and individual interaction within them - Noura Saleh Albahijan; Hessa Abdullah Alsuraibi; Rawan Al-Qarawi (International Journal of Computers and Informatics, 2025)
This paper, entitled “Smart Learning Environments: Their Concept, Educational Contexts, Student Experiences, Technical and Pedagogical Components, Philosophical Foundations, Learning Theories, and Individual Interaction through Social Media Tools and Online Meetings”, employs the descriptive-analytical method. The paper is structured into six main sections: The first addresses the concept of smart learning environments; the second discusses their characteristics; the third highlights their advantages; and the fourth explores their technical and pedagogical components. The fifth section examines learning and instructional theories and their role in designing smart learning environments, with a focus on modern educational philosophies and their impact on enhancing the learning process. The sixth discusses individual interaction through digital tools and virtual meetings, emphasizing the role of smart platforms in enriching the educational experience. The paper concludes by presenting the main challenges facing these environments and suggesting solutions to achieve adaptive and interactive learning.
Keywords: Smart Learning Environments; Smart Education; Smart Teaching